Propane and Naphthalene Oxidation over Gold-Promoted Cobalt Catalysts Supported on Zirconia - Leguizamón Aparicio, María Silvia del Valle (2020)
Zirconia-supported gold-promoted cobalt catalysts were synthesized and tested for the complete oxidation of propane and naphthalene. The catalysts were characterized by BET surface area, scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), powder X-ray diffraction (XRD), transmission electron microscopy (TEM), temperature-programmed reduction (TPR), and X-ray photoelectron spectroscopy (XPS). In both propane and naphthalene combustion reactions, the results obtained indicate that catalysts formulated with Co3O4 are more active than those containing only Au. Catalysts prepared using the deposit/precipitation (DP) method have better activity than those in which the traditional technique is used. Gold addition using the DP methods generates a promoting effect on the activity of cobalt-containing catalysts. The AuDpCoZt catalyst was found to be the most active for both propane and naphthalene combustion. The catalytic behavior of this sample is associated with a synergic effect between gold, cobalt, and the support, which is also evidenced by an increase in the reducibility of this catalytic system. The effect of the presence of NO in the feed was also analyzed for propane combustion.